2015
DOI: 10.1037/a0035706
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity ideology and psychological strain: Considering men’s social stressors in female-dominated occupations.

Abstract: According to the gender role strain paradigm (GRSP), men's adherence to masculinity ideology could result in dysfunction strain when it becomes incompatible with other role demands. To support the relevance of GRSP in the work context, we explored the relationship between masculinity ideology and strain for men in female-dominated occupations by introducing social stressors as an intervening variable. Within female-dominated occupations, the feminine gender role can be seen as a crucial job requirement and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…In the U.S. and Scandinavia, researchers have found that whereas some men have experienced mistrust, narrowed career opportunities, and challenges to their manhood (e.g., Allan 1993;Henson and Rogers 2001;Soerlie et al 1997), others report having been welcomed and offered enhanced career opportunities, including swift advancement, and choice trainings and placements (Hultin 2003;Sargent 2001;Williams 2013). Researchers in the U.S., Canada, Germany, and the U.K. have also found that interactions around gender role issues in female dominated work environments can increase men's distress due to Gender Role Conflict (Dodson and Borders 2006;Henson and Rogers 2001;Luhaorg and Zivian 1995;Simpson 2005) and gender role strain (Sobiraj et al 2015).…”
Section: Experiences Within the Workplacementioning
confidence: 98%
“…In the U.S. and Scandinavia, researchers have found that whereas some men have experienced mistrust, narrowed career opportunities, and challenges to their manhood (e.g., Allan 1993;Henson and Rogers 2001;Soerlie et al 1997), others report having been welcomed and offered enhanced career opportunities, including swift advancement, and choice trainings and placements (Hultin 2003;Sargent 2001;Williams 2013). Researchers in the U.S., Canada, Germany, and the U.K. have also found that interactions around gender role issues in female dominated work environments can increase men's distress due to Gender Role Conflict (Dodson and Borders 2006;Henson and Rogers 2001;Luhaorg and Zivian 1995;Simpson 2005) and gender role strain (Sobiraj et al 2015).…”
Section: Experiences Within the Workplacementioning
confidence: 98%
“…In addition to such domain-specific ability stereotypes, parents may also hold stereotypical beliefs about what roles men and women should occupy in society. Specifically, such gender role beliefs may translate into conceptions that men should seek status and avoid feminine activities, or that women tend to be emotional and dependent (Sobiraj et al, 2015;Levant et al, 2017). Therefore, beyond stereotypes about ability in different domains, which are likely to affect boys' and girls' self-concepts in these domains, gender role beliefs may have implications for the types of occupational interests parents encourage or discourage, and thus make a unique contribution to students' values and aspirations toward stereotypical or counter-stereotypical domains.…”
Section: Parents As Transmitters Of Gender Stereotypesmentioning
confidence: 99%
“…When access to male-typed occupations is limited for men of working class background or racial minorities, entering female-dominated occupations can provide an alternative path for social mobility (Yavorsky et al, 2016;Seehuus, 2019). Yet, a lack of endorsement of the gender-atypical occupational role renders the "finders" also more vulnerable to role strain or to anxiety for stigmatization (Lupton, 2006;Sobiraj et al, 2015). Thus, how working in female-dominated occupations is perceived depends partly on foregoing selection processes (Simpson, 2005).To tackle the selection problem, I turn to the compulsory civilian service as its suspension provides exogenous variation in men's exposure to learning experiences in female-dominated domains.…”
Section: Men's Experiences In Gender-atypical Occupationsmentioning
confidence: 99%